(untitled) (Research, Society and Development, 2022)
Photosynthetic purification using microalgae cultures has emerged as an efficient technology for the removal of carbon dioxide from biogas. In this method, microlagoons capture CO2 via photosynthesis and release O2 into the culture medium, which is used by sulfur-oxidizing bacteria to oxidize H2S to sulfates. The objective of this research was to evaluate the purification of biogas by the photosynthetic process of microalgae. For this, a prototype of a pilot scale purifier was developed. The experimental setup consisted of a two-stage system, one consisting of a microalgae culture photobioreactor connected to an absorption column. The liquid was circulated in a descending manner, returning to the photobioreactor at the bottom of the column. The biogas was injected into the absorption column in a counterflow regime to the liquid. The analyzes were carried out focusing on the gases CO2, CH4 and O2, present in the influent and effluent biogas to the absorption column. In raw biogas, the CO2 concentration was around 32%; CH4 ranged from 63.08% to 64.32%; and O2 from 0.17% to 0.71%. The purified biogas had CO2 concentrations ranging from 9.15% to 18.46%; CH4 from 71.4% to 76.2%; and O2 between 1.24% to 3.26%. CO2 removal efficiencies of 42.46% to 72.02% were recorded in the purified biogas. The results showed that the proposed prototype using the biological process with microalgae proved to be satisfactory and promising for the purification of biogas.